1975
DOI: 10.1037/h0076658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol on human performance: An integration of research findings based on an abilities classification.

Abstract: The tasks used in 41 studies of the effects of alcohol on human performance were classified in terms of the abilities required for task performance. For each category of task, median performance computed across all studies within the category was plotted as a function of both dosage and the time between alcohol administration and task performance. It was found that the curves relating performance to dosage differed as a function of the ability requirements of the task. The effects on performance of time from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

1979
1979
2015
2015

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 7 publications
1
31
0
2
Order By: Relevance
“…The results of this study suggested that alcohol had marginally significant B-7 negative effects on tracking and on vigilance performance. The authors suggested that the negative effects were stronger for the vigilance task, as opposed to the tracking task --consistent with many but not all reviews of the alcohol performance literature (see Levine, Kramer, and Levine, 1975).…”
Section: Acute Effects Of Alcohol On Task Performancementioning
confidence: 51%
“…The results of this study suggested that alcohol had marginally significant B-7 negative effects on tracking and on vigilance performance. The authors suggested that the negative effects were stronger for the vigilance task, as opposed to the tracking task --consistent with many but not all reviews of the alcohol performance literature (see Levine, Kramer, and Levine, 1975).…”
Section: Acute Effects Of Alcohol On Task Performancementioning
confidence: 51%
“…Resultados diferentes e por vezes contraditórios podem ser encontrados para experimentos de ingestão alcoólica, constatando inclusive que o álcool pode ter efeitos diferenciados em diversas frequências sonoras, alterando ou não a percepção das mesmas, o que podem ser explicado de alguma maneira pelas distintas formas com que são feitos o controle e a medida da concentração alcoólica (Carpenter, 1962;Eggleton, 1941;Himwich, 1957;Hogan & Linfi eld, 1983;Levine, Kramer, & Levine, 1975;Wallgren & Barry, 1970).…”
Section: Discussionunclassified
“…Les principes de base de son utilisation en éducation avaient déjà été évoqués parThorndike (1933) dans sa recherche de la découverte d'une valeur commune à différentes études relatives au lien entre deux variables continues. Par la suite, Levine, Romashko et Fleishman, (1971) ainsi que Levine, Kramer et Levine (1975 ) ont à leur tour eu recours à des méthodes visant à trouver une valeur commune à différentes études effectuées sur un même sujet. Mais revient à Glass (1976) le mérite d'avoir introduit une méthodologie systématique et rigoureuse de la méta-analyse en éducation.…”
Section: Problématiqueunclassified